Enhancing food resilience in the age of geoeconomics by applying biomimetic principles in urban agriculture - Alex Toth (Social Sciences and Humanities Open, 2025)
Biomimicry, though still emerging within the social sciences, offers promising insights for rethinking food security by drawing analogies from natural ecosystems and reconnecting with traditional ecological knowledge. This paper argues that adopting urban agroecological strategies rooted in biomimicry can significantly enhance resilience to geoeconomic pressures, supply chain disruptions, and environmental shocks. As geopolitical tensions intensify, exacerbated by climate change, pandemics, and urbanization, the strategic role of food as a tool of influence is poised to grow, with cities particularly vulnerable due to their reliance on external food supplies. Urban agroecology, inherently biomimetic and regenerative, is presented as a scalable and context-sensitive pillar for building more resilient and self-sustaining food systems. By embracing principles of ecological regeneration such as biodiversity, circularity, and interdependence, this approach restores vital ecosystem functions while strengthening food system stability. The paper explores how a biomimetic approach to urban agriculture can serve as a strategic mechanism for food security, especially in urbanized and geopolitically sensitive regions, with particular attention to emerging models from the Global South. It further examines how states and cities could prepare for supply shocks and highlights the untapped potential of localized, regenerative food production as a transformative response to rising vulnerabilities.